Sivelestat Alleviates Atherosclerosis by Improving Intestinal Barrier Function and Reducing Endotoxemia - Nie, Hezhongrong; Xiong, Qingquan; Lan, Guanghui; Song, Chunli; Yu, Xiaohong; Chen, Lei; Wang, Daming; Ren, Tingyu; Chen, Zeyan; Liu, Xintong; Zhou, Yiwen (Frontiers in Pharmacology, 2022)
Emerging evidence suggests that atherosclerosis, as one of leading phenotypes of cardiovascular diseases, is a chronic inflammatory disease. During the atherosclerotic process, neutrophils play critical roles in vascular inflammation and plaque formation. Meanwhile, gastrointestinal disorder is considered a risk factor in mediating atherosclerotic process. The present study aimed to utilize sivelestat, a selective inhibitor of neutrophil elastase, to investigate its pharmacological benefits on atherosclerosis and disclose the gastrointestinal-vascular interaction. The activation of intestinal neutrophil was increased during atherosclerotic development in western diet-fed ApoE-/- mice. Administration of sivelestat attenuated atherosclerotic phenotypes, including decreasing toxic lipid accumulation, vascular monocyte infiltration, and inflammatory cytokines. Sivelestat decreased intestinal permeability and endotoxemia in atherosclerotic mice. Mechanistically, sivelestat upregulated the expression of zonula occludens 1 in the atherosclerotic mice and recombinant neutrophil elastase protein-treated intestine epithelial cells. Meanwhile, treatment of sivelestat suppressed intestinal expression of inflammatory cytokines and NF-κB activity. In the contrast, administration of lipopolysaccharides abolished the anti-atherosclerotic benefits of sivelestat in western diet-fed ApoE-/- mice. In clinical study, circulating endotoxin level and intestinal neutrophil elastase activity were positively correlated with carotid intimal media thickness. In conclusion, sivelestat had pharmacological application in protecting against atherosclerosis, and intestinal homeostasis played one of the critical roles in atherosclerotic development.